Cálculo y medición de las reacciones en los bloques de la cama de - Espinosa Terán, Fernando Xavier (2010)
The Andes V tanker ship of 96 m in length was stranded on the Napo ASTINAVE Dam in April 2010. In this work we have calculated the reactions of the bed blocks stranding the vessel referred to by three theoretical methods: Crandall, and Timoshenko Beam Finite Element. In addition, these reactions have been estimated experimentally by measuring the crushing of the planks on top of each block. In preparing of the bed for B / V T Andes, found improper practices such as recycling and use of worn and the boards of different heights, which did not allow adequate data collection. So strange results were obtained as negative reactions, and they had to select results that appear to be reasonable. The experimental results of the reactions are in the range of theorists, and also grow into Popa, a trend also seen in the theoretical process (133 and 142 ton as Timoshenko beam and MEF, respectively). This shows that, despite the difficulties, general theoretical estimates are consistent with the experimental. Then considering the consistency in values, and the trend of the reactions, it is concluded that both the MEF and the Timoshenko beam for analysis of reactions are adequate, although the latter is recommended because it requires less time for model development